Stargazing - Wang, Jen, 1984- (First Second, 2019)
Moon's family has moved in next door to Christine's, which means Moon and Christine have graduated from friends to best friends. With that new title comes new secrets--and Moon confesses to Christine that she sometimes has visions of celestial creatures who give her messages from space, telling her that Earth is not her true home. Catastrophe then strikes, and now Christine finds herself not relying on Moon, but being the one Moon needs to rely on for hope and support.